AODTU-009 Therapeutic action of ketogenic enteral nutrition in obese and overweight patients: a retrospective interventional study. (17th June 2017) - Papadia, C; Basset, P; Cappello, G; Shidrawi, R
Abstract : Introduction: Ketogenic Enteral Nutrition (KEN) is a modification of Blackburn's protein-sparing modified fast, using a hypocaloric, ketogenic liquid diet. The study is a retrospective analysis that examines safety, weight loss and body composition changes after sequential 10 days cycles of KEN therapy. Method: Anthropometric and bio-impedance data from 629 patients who underwent KEN were collected before and after completing a ten-day cycle. The study focuses on the change in outcomes from the first cycle to the second cycle and from the first cycle to the third cycle. The following outcomes were explored: weight, waist circumference, BMI, fat mass, lean mass, dry lean mass, phase angle, wellness marker, water mass as a percentage of total body weight. The cycle 1, 2 and 3 outcomes were analysed using descriptive statistics (mean, standard deviation, n) summarising the outcome at each cycle. Statistical tests were used to test for significant differences between paired cycle 1 and cycle 2 outcomes and also between paired cycle 1 and cycle 3 outcomes. For normally distributed outcomes, the paired t-test was used. Whereas for skewed outcomes, the Wilcoxon signed-ranks test was used. Scatter plots were used to plot percentage of excess weight loss against phase angle. The Pearson's correlation coefficient was also calculated. Results: The results suggested significant changes for all analysed parameters. There were significant decreases in weight, waist circumference, BMI, fat mass, lean mass, dry lean mass and phase angle. Quantitative changes in lean mass and dry lean mass were negligible with respect to changes in fat mass. There was also a statistically significant increase in water mass as a% of total body weight and wellness marker from cycle 1 to cycle 3. The Pearson's correlation coefficients r=0.18, p=0.004 and r=22, p=0.04 indicated changes in cycle 1 and cycle 3 in percentage of weight excess to be significantly, positively correlated to baseline phase angle. KEN treatment was well tolerated. 92% of patients on oral hypoglycaemics and 80% of patients on anti-hypertensive medication were able to discontinue their medication safely during KEN therapy Conclusion: KEN treatment is safe, well tolerated and results in rapid fat loss without detriment to dry lean mass. There was found to be a statistically significant positive association between percentage of excess weight loss and baseline phase angle. Disclosure of Interest: C. Papadia: None Declared, P. Basset: None Declared, G. Cappello: None Declared, R. Shidrawi Conflict with: Director weight management system limited